Moskowitz syndrome manifesting as recurrent large vessel strokes in a young male-An original research paper (Academia Journal of Medicine, 2024)
Background: Thrombotic thrombocytopenic purpura (TTP) is a rare and  life-threatening condition characterized by microthrombus formation due to a  deficiency of ADAMTS13, which cleaves von Willebrand factor multimers. This  deficiency leads to widespread microangiopathic hemolytic anemia and multiple  organ involvement, particularly affecting the brain, heart, and kidneys. TTP can  present atypically and poses a diagnostic challenge, especially in young patients  with neurological symptoms and thrombocytopenia. Early diagnosis and prompt  initiation of plasma exchange therapy (PEX) and steroids are critical to reduce  mortality. Case Report: A 17-year-old male presented in an altered state with weakness in  the right upper arm and bilateral lower limbs for 4 days. He had a history of fever  and convulsions 4 days prior, with two previous convulsive episodes in the last two  years, both of which had resolved without neurological deficits. On examination,  the patient was febrile, tachycardic, and drowsy, with left gaze palsy and significant  weakness in the right upper limb and both lower limbs. The patient had lost bowel  and bladder sensation, and plantar reflexes were bilaterally upgoing.An MRI of  the brain with angiogram revealed acute large vessel occlusion in the bilateral  anterior cerebral artery (ACA) territory and gliosis in the right middle cerebral  artery (MCA) region. Laboratory investigations showed severe thrombocytope nia (platelet count 23k/cumm), anemia (Hb 6.2 g/dL), elevated LDH (1597 U/L),  and increased cardiac troponin (35 pg/mL). The patient was diagnosed with TTP  and was promptly started on plasma exchange therapy and high-dose steroids. His  sensorium improved within 2 days, though weakness persisted. Plasma exchange  therapy was continued daily for 11 days, resulting in gradual improvement.
Keywords: TTP - Thrombotic Thrombocytopenic Purpura; vWF - von Willebrand Factor; PEX- Plasma Exchange Therapy; ADAMTS13 - A Disintegrin and Metalloprotease with Thrombospondin type 1 motif member 13 HUS - Hemolytic Uremic Syndrome; PLASMIC- Platelet count, hemolysis; absent kidney injury absence of active cancer presence of mycoplasma; and no other cause of thrombocytopenia score; ISTH - International Society on Thrombosis and Haemostasis